Charlotte Cushman papers - Cushman, Charlotte, 1816-1876.
Correspondence; biographical and genealogical material; annotated scripts and texts of plays, poetry, and readings; newspaper clippings; reviews; souvenir programs; and other papers relating chiefly to Cushman's career in the theater in the United States and in London, England. During Cushman's residence in Rome, Italy (1856-1870), her correspondence relates chiefly to theatrical matters but also reflects the reaction of Americans abroad to the U.S. Civil War and Abraham Lincoln's assassination. Includes reviews chronicling her career and scripts for her most well-known Shakespearean roles and material on Cushman's American tour for the benefit of the United States Sanitary Commission in 1863.
Correspondents include Henry W. Bellows, John Bigelow, Edwin Booth, Elizabeth Barrett Browning, Jane Welsh Carlyle, Henry Fothergill Chorley, Wayman Crow, Charles Augustus Cushman, Edwin Charles Cushman, Emma Crow Cushman, Mary Eliza Cushman, James Thomas Fields, Thomas Wentworth Higginson, Julia Ward Howe, Helen Hunt Jackson, Geraldine Endsor Jewsbury, Fanny Kemble, Rufus King, Henry Wadsworth Longfellow, William Charles Macready, Christine Nilsson, John Howard Payne, Anna Wharton Seward, William Henry Seward, William T. Sherman, Emma Stebbins, Thomas Adolphus Trollope, Martin Van Buren, Lester Wallack, and John Greenleaf Whittier.
Microfilm edition (negative only) of Hamlet prompt book available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Actress.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bellows, Henry W. -- 1814-1882 -- Correspondence; Bigelow, John, -- 1817-1911 -- Correspondence; Booth, Edwin, -- 1833-1893 -- Correspondence; Browning, Elizabeth Barrett, -- 1806-1861 -- Correspondence; Carlyle, Jane Welsh, -- 1801-1866 -- Correspondence; Chorley, Henry Fothergill, -- 1808-1872 -- Correspondence; Crow, Wayman, -- 1808-1885 -- Correspondence; Cushman, Charles Augustus, -- 1818-1896 -- Correspondence; Cushman, Edwin Charles, -- 1838- -- Correspondence; Cushman, Emma Crow, -- 1840?- -- Correspondence; Cushman, Mary Eliza, -- 1793-1866 -- Correspondence; Fields, James Thomas, -- 1817-1881 -- Correspondence; Higginson, Thomas Wentworth, -- 1823-1911 -- Correspondence; Howe, Julia Ward, -- 1819-1910 -- Correspondence; Jackson, Helen Hunt, -- 1830-1885 -- Correspondence; Jewsbury, Geraldine Endsor, -- 1812-1880 -- Correspondence; Kemble, Fanny, -- 1809-1893 -- Correspondence; King, Rufus, -- 1814-1876 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Longfellow, Henry Wadsworth, -- 1807-1882 -- Correspondence; Macready, William Charles, -- 1793-1873 -- Correspondence; Nilsson, Christine, -- 1843-1921 -- Correspondence; Payne, John Howard, -- 1791-1852 -- Correspondence; Seward, Anna Wharton -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Shakespeare, William, -- 1564-1616 -- Dramatic production; Sherman, William T. -- 1820-1891 -- Correspondence; Stebbins, Emma, -- 1815-1882 -- Correspondence; Trollope, Thomas Adolphus, -- 1810-1892 -- Correspondence; Van Buren, Martin, -- 1782-1862 -- Correspondence; Wallack, Lester, -- 1820-1888 -- Correspondence; Whittier, John Greenleaf, -- 1807-1892 -- Correspondence; United States Sanitary Commission; Acting; Americans -- Italy -- Rome -- History -- 19th century; Benefit performances -- United States -- 19th century; Drama; Theater -- England -- London -- History -- 19th century; Theater -- United States -- History -- 19th century; United States -- History -- Civil War, 1861-1865 -- Foreign public opinion; Actresses